The effects of switching EGFR‐TKI treatments for non‐small cell lung cancer because of adverse events. Issue 2 (2nd December 2018) - Sakata, Yoshihiko; Kawamura, Kodai; Shingu, Naoki; Hiroshige, Shigeo; Yasuda, Yuko; Eguchi, Yoshitomo; Anan, Keisuke; Hisanaga, Junpei; Nitawaki, Tatsuya; Nakano, Aiko; Ichikado, Kazuya
Abstract: Background: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) are used to treat patients with non‐small cell lung cancer (NSCLC) and EGFR driver mutations. Although some patients discontinued these treatments because of adverse events, it is unclear whether switching EGFR‐TKI because of adverse events provides a benefit. Methods: This retrospective study evaluated data from 22 patients with EGFR mutation‐positive NSCLC who received at least two EGFR‐TKIs that were switched because of adverse events (March 2011 to September 2017). Progression‐free survival 2 (PFS2) was defined as the time from starting of the first EGFR‐TKI treatment to disease progression during the second EGFR‐TKI treatment. Results: Seventeen patients received gefitinib as the first EGFR‐TKI treatment, while four patients received afatinib and one patient received erlotinib. The median time to failure of the first EGFR‐TKI treatment was 1.6 months. The EGFR‐TKIs were switched because of hepatotoxicity ( n  = 16), interstitial lung disease ( n  = 3), and other reasons ( n  = 3). The median washout period was 1.1 months. Seventeen patients received erlotinib as the second EGFR‐TKI treatment, while three patients received gefitinib and two patients received afatinib. The median PFS for the second EGFR‐TKI treatment was 15.2 months. The median PFS2 was 17.7 months and the median overall survival was 32.8 months. Conclusions: Switching EGFR‐TKIs because of adverse events provided a clinical benefit for patients with EGFR mutation‐positive NSCLC. Appropriate judgment regarding switching from one EGFR‐TKI to another may improve the performance status and prognosis of patients with EGFR mutation‐positive NSCLC.